POVERTY, INCOME INEQUALITY AND GROWTH IN NIGERIA: LOOKING BEYOND NOW - OKUTIMIREN, ADETEJI; Okuneye, Babatunde Adekunle; Ajayi, Felix Odunayo (The European Journal of Applied Economics, 2024)
The Nigerian population’s well-being is significantly influenced by poverty, income inequality, and economic growth, which are interconnected issues. While addressing the immediate needs of those living in poverty is important, it is equally essential to examine the long-term causes of poverty and inequality. This study utilizes the autoregressive distributed lag (ARDL) approach to investigate the impact of poverty and income inequality on economic growth, using data from 1986 to 2020. The study found that income inequality positively affects economic growth, while poverty negatively impacts economic growth in the long run. The study recommends that the government develop comprehensive policies and programmes that create a favorable environment for growth. These policies should be inclusive and address the specific needs of the poor, providing them with opportunities to access education, healthcare, and employment.